Economical sustainability of integrated photo voltaic and hydroponic systems for rural areas - Fitria Yulistiani; Conny K Wachjoe; Hermagasantos Zein; Annisa Syafitri Kurniasetiawati; Teguh Sasono; Yanti Suprianti (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2022)
Hydroponic plantations are an effort of future agricultural technology, and this is due to population growth and increasingly saving agricultural land. Besides that, hydroponics can trigger rural economic development by opening employment opportunities for rural areas. The realization of hydroponics in rural areas that are not connected to the grid can use solar energy to circulate water continuously. The components of photo voltaic systems have been designed to the needs of the hydroponic system. Photo voltaic technology has been used for a long time for lighting in remote areas. Integrating the photo voltaic system with hydroponics is a synergistic effort to use energy productively. The case the demand for vegetables in rural areas is minimal, with limited land and the level of land productivity that depends on the availability of fertilizers. The economical method for analyzing the integrating system of photovoltaic and hydroponic systems is based on PBP, CCP, and ROROI. The results obtained for kale based on the PV-hydroponic integration system have a return on investment (PBP) of 13.5 months, cumulative cash posit (CCP) of 1.84, and Rate of Return on Investment (ROROI) of 8.01%. Adding the second and third hydroponic plant modules can reduce PBP to 6.2 months and 5.2 months, respectively. Likewise, CPP increased from 1.84 to 3.68 and 5.21, respectively. Meanwhile, ROROI rose from 8.01% to 11.43% and 13.34%, respectively.